MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI BIMBINGAN BELAJAR DI DUSUN GOMBONG KABUPATEN MAGELANG - Arvina Istiqomah; Faiq Yunianto (khidmatan, 2024)
This Community Service (PkM) activity was carried out in Gombong Hamlet, Magelang Regency, with the primary goal of increasing student learning motivation which had declined due to the ineffectiveness of online learning. The program was designed to fill the academic gap, complementing existing character development efforts. The methodology employed was the Asset-Based Community-Driven Development (ABCD) approach, where the problem of low motivation was addressed through the design and implementation of interactive Tutoring (Bimbingan Belajar) sessions. Tutoring was held six days a week, utilizing a personal mentoring model at the local mosque porch. The sessions involved adaptive and engaging learning strategies, including task completion, additional cross-curricular material, and interspersed games and singing to combat lack of focus. The results of the PkM demonstrated the program's success, marked by a significant increase in student enthusiasm and attendance, along with positive feedback from parents who felt assisted in academic guidance. This achievement confirms that structured and responsive tutoring intervention is an effective solution for reinforcing student motivation and academic competence at the hamlet level.